(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the impact of monopolies on the market economy and the effectiveness of competition policy. Monopoly is a market structure in which one or several firms determine the price and output of goods or services in the absence of market competition. Market efficiency is shaped by the presence or absence of competition. Competition policy includes government measures aimed at reducing the negative effects of monopolies, creating a healthy competitive environment, and ensuring consumer welfare. The article highlights the mechanisms of competition policy in the national economy, their effectiveness, and practical outcomes.